The importance of whey protein levels of Klotho and fibroblast growth of factor-23 (fgf-23) as early diagnostic markers of chronic kidney damage - L. Yu. Milovanova; S. Yu. Milovanova; D. V. Kryukova; S. V. Moiseev; L. V. Kozlovskaya (Сеченовский вестник)
The purpose of the study is to investigate the clinical significance of determination of serum FGF-23 and Klotho in patients with different stages of chronic kidney disease (CKD). Materials and Methods: The study included 70 patients with CKD stages 1–5D (30 men and 40 women, mean age 41,0–6,7 years), in whom the serum levels of FGF-23 and Klotho, as well as work Ca х P and the content of intact parathyroid hormone (iPTH). Results: the progression of CKD from stage 1 to 5D serum concentration of FGF-23 was increased, and the concentration of Klotho decreased. Glomerular filtration rate (GFR) was directly correlated with the serum concentration of FGF-23 (r=0,693, p <0,01) and back — with a protein concentration of Klotho (r=-0,799, p <0,01). Increased levels of FGF- 23 as GFR decline began in CKD stage 3 and outpaced the increase in serum levels of phosphorus and iPTH, which increased in CKD stage 4–5. In 49 patients with CKD and hypertension increase the degree of BP directly correlated with the serum concentration of FGF-23 (r=0,452; p <0,01) and back — with the serum concentration of Klotho (r=-0,687; p <0,01). In addition, changes in the levels found a link of FGF-23 and Klotho with increasing thickness of the posterior wall of the left ventricle, the frequency of detection of calcifications in the heart and major arteries and anemia. Conclusion: These results suggest the possibility of practical application of Klotho and FGF-23 levels as an early diagnostic marker of kidney damage for prognosis and improve cardio-renoprotective strategies.